Depiction of Bharavahakas (load bearers) - Temples of India Project Team (Jio Institute, 2024)
At the upper part of both pilasters, bharavahakas (load bearers) are depicted. Interestingly, the bharavahaka on the right pilaster is shown playing the flute.